The having objection to bundle theories of subjects of experience. - O'Conaill, Donnchadh (Philosophical Quarterly, 2024)
The self or subject of experiences is often regarded as a mysterious entity, prompting approaches that seek to deflate it, metaphysically speaking. One such approach is the bundle theory, the most well-known version of which holds that each subject is a bundle of experiences. This version of the bundle theory seems vulnerable to the having objection: since subjects have experiences, they cannot be identical with bundles of experiences. I shall argue that while the having objection is intuitively plausible, its dialectical force is limited since it does not work without substantial further metaphysical assumptions.